(untitled) (Research, Society and Development, 2025)
This study evaluates the textbook English in Action 1 to assess its effectiveness in developing reading, writing, listening, and speaking skills at the CEFR A1 level. Aimed at serving as a model for novice teachers, the research addresses the broader pedagogical goal of ensuring that English as a Foreign Language coursebooks promote authentic, communicative, and well-scaffolded learning experiences. Employing a qualitative methodology, the analysis draws on rubrics and checklists from established literature to evaluate skill-specific components and their coherence with stated objectives. Each of the textbook’s eight units was examined in terms of text quality, task design, authenticity, scaffolding, and communicative relevance. The findings indicate that while the textbook shows strong alignment with CEFR A1 descriptors in listening and speaking, it demonstrates notable weaknesses in writing authenticity, reading text variety, and opportunities for spontaneous learner output. Pronunciation and strategy instruction are also underdeveloped. Despite these limitations, the coursebook provides a clear framework for foundational language development and can be considered a practical resource for beginner learners. However, its effective classroom implementation depends on teacher mediation and the inclusion of supplementary materials to enhance learner autonomy, critical thinking, and engagement with real-world communicative tasks.